Pengaruh Model Pembelajaran PAIKEM GEMBROT terhadap Hasil Belajar PKn Siswa Kelas IV SD - Wahyu Ragil Catur Saputro; Ramanata Disurya; Adrianus Dedy (Journal on Education, 2023)
This study aims to determine the effect of the PAIKEM GEMBROT learning model on the learning outcomes of Civics grade IV elementary school students. This research method uses an experimental method with the research design used is nonequivalent control group design using pretest and posttest. The research population in this study was all grade IV students of SD Negeri 14 Makarti Jaya totaling 42 students. The population continued with a sample of 21 students for the experimental class and 21 students for the control class. Based on the results of the data testing analysis, the average pretest score was 46.76 and the posttest score was 63.48, then the experimental class score was the average pretest score of 47.00 and the posttest score was 78.95 with the conclusion that there were differences in student learning outcomes. Based on the output value of the independent sample t-test, the significance value is 0.001 < α (α = 0.05) and tcount > ttable or 3.715 > 2.201, then reject H0 and accept Ha. So it can be concluded that there is a significant influence of the PAIKEM GEMBROT learning model on the learning outcomes of Civics grade IV elementary school students.